2021
DOI: 10.1039/d1na00452b
|View full text |Cite
|
Sign up to set email alerts
|

Inherent heterogeneities and nanostructural anomalies in organic glasses revealed by EPR

Abstract: Intriguing heterogeneities and nanostructural reorganizations of glassy ionic liquids (ILs) have recently been found using electron paramagnetic resonance (EPR) spectroscopy. Alkyl chains of IL cations play the key role in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 75 publications
4
20
0
Order By: Relevance
“…Spectra in Fig. 1 may be assigned to a mixture of immobile and mobile tempone components (see simulations of the analogous spectra performed for glassy ILs in Fedin's group 23–31 ). The appearance of three isosbestic points (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectra in Fig. 1 may be assigned to a mixture of immobile and mobile tempone components (see simulations of the analogous spectra performed for glassy ILs in Fedin's group 23–31 ). The appearance of three isosbestic points (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Spin-probe EPR, in its conventional continuous wave (CW) version and in the pulsed version of electron spin echo (ESE) spectroscopy, has been shown to be a promising tool for elucidating features of molecular packing in glassy ILs. 23–31 In these studies, density/rigidity heterogeneities in ILs were found near the glass transition temperature ( T g ), with nanostructural anomalies revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that some non-IL compounds, such as those mimicking imidazolium cations, also exhibit similar structural anomalies. In particular, this was clearly evidenced experimentally for phthalates [ 14 ]. However, despite the clear role of alkyl chains, the mechanism of such anomalies is still far from being understood.…”
Section: Introductionmentioning
confidence: 66%
“…Molecular Dynamics (MD) simulations are and have been actively employed to understand the local structures and dynamics of various molecular liquids and their glasses [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Therefore, we used MD in an attempt to explain the structural anomalies previously observed in ILs [ 11 ] and phthalates [ 14 ]. The MD studies of ILs are more challenging compared to phthalates, because of the precise treatment required due to the charged nature of ILs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation